Catálogo comentado das espécies de abelhas do gênero Eulaema Lepeletier, 1841 (Hymenoptera: Apidae) (Lundiana: International Journal of Biodiversity, 2008)
The taxonomic information on the species of Eulaema Lepeletier, 1841 is updated. Three of the species recently described by Moure — E. pallescens Moure, 2000, E. stenozona Moure, 2000 and E. helvola Moure, 2000 — are synonymized with E. meriana (Olivier, 1789), E. terminata (Smith, 1874) and E. seabrai Moure, 1960, respectively. Two species revalidated by Moure (2000), E. quadrifasciata (Friese, 1903) and E. niveofasciata (Friese, 1899), are considered synonyms of E. meriana (Olivier, 1789) and E. bombiformis (Packard, 1869), respectively. Besides, E. mimetica Moure, 1967 is considered a synonym of E. tenuifasciata (Friese, 1925). Additions to the catalogue by Moure (2000) include Eulaema sororia Dressler & Ospina-Torres (1997) and E. chocoana Ospina-Torres & Sandino-Franco (1997), which were not mentioned by Moure (opus cit.), and E. napensis Oliveira, 2006, E. parapolyzona Oliveira, 2006 and E. pseudocingulata Oliveira, 2006, described after the publication of his catalogue. Lectotypes of E. boliviensis Friese, 1898, E. bomboides (Friese, 1923), E. polyzona (Mocsary, 1897) and E. tenuifasciata (Friese, 1925) are designated. Comments on the known geographic distributions of the 25 regonized species and maps illustrating them are also presented.Keywords: Neotropics, orchid-bees, taxonomy, geographic distribution, lectotype designation.